Dentist as an Expert Witness under Section. 45 of Indian Evidence Act 1872 - S.Rajkumari; R.Mensudar; B.Thayumanavan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dentists of different specialties are sought for their expert testimony in person identification, injury relatedto oral and dental structures. Person identification may include live or dead, injured or healthy, skeletonized,or mummified. Dentists also opine in crime scene investigation, mass disaster victim identification, andprofessional negligence or injury. The dental surgeon evaluates the available dental evidence and drafts areport to testify in a deposition as a professional opinion in the medico-legal cases. This article discusses thedemeanor of the dental surgeon as an expert in the court of law.